Analyzing the Effect of FOMO on Students’ Learning Motivation in Islamic Religious Education - Arini, Arini; Hudha, Mokhamad Choirul (Southeast Asian Journal of Islamic Education, 2025)
This research aims to know the effect of the FOMO phenomenon on learning motivation and student well-being in SMA Muhammadiyah Batusangkar, especially in PAI learning. Employing qualitative approaches, twelve students, four PAI teachers, and the principal in the school participated in the research. The data collection techniques used in this study were interviews, classroom observations, and documentation of academic documents and student records. Thematic analysis was conducted to identify emerging patterns and impacts of FOMO on learning motivation, concentration, and student well-being. The findings exhibit that FOMO of students disrupts learning motivation and student well-being, anxiety about missing out on social media trends makes learning focus low, while increasing procrastination. FOMO has a detrimental effect on concentration, enjoyment of learning, and the application of religious teachings. Student spends more time on social media and watching viral trends, which minimizes study time, and it then affects their grades in school and their relationship with others in real-life interaction. SMA Muhammadiyah Batusangkar can overcome the impact of FOMO by social media education that is wise, character education based on Pancasila values, and a guidance and counseling approach that applies to the decrease in student anxiety. The implications of this study are the necessity of enacting education for wise social media management and rebuilding Pancasila values by instilling such values through guidance and counseling to cut down the negative effects of FOMO.